2016
DOI: 10.1523/jneurosci.1469-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Adult Brain Serotonin Deficiency Causes Hyperactivity, Circadian Disruption, and Elimination of Siestas

Abstract: Serotonin (5-HT) is a crucial neuromodulator linked to many psychiatric disorders. However, after more than 60 years of study, its role in behavior remains poorly understood, in part because of a lack of methods to target 5-HT synthesis specifically in the adult brain. Here, we have developed a genetic approach that reproducibly achieves near-complete elimination of 5-HT synthesis from the adult ascending 5-HT system by stereotaxic injection of an adeno-associated virus expressing Cre recombinase (AAV-Cre) int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 69 publications
7
56
0
Order By: Relevance
“…Young adult mice (∼8 weeks of age) underwent a single survival intracranial surgical procedure to receive adeno-associated virus (AAV) as described in Whitney et al (2016). After induction in isoflurane anesthetic (3.0–3.5% in 1 l/min O 2 ), the mice were mounted into a stereotaxic frame and the anesthetic state was maintained under isoflurane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Young adult mice (∼8 weeks of age) underwent a single survival intracranial surgical procedure to receive adeno-associated virus (AAV) as described in Whitney et al (2016). After induction in isoflurane anesthetic (3.0–3.5% in 1 l/min O 2 ), the mice were mounted into a stereotaxic frame and the anesthetic state was maintained under isoflurane.…”
Section: Methodsmentioning
confidence: 99%
“…To accomplish this, we used a recently established conditional approach (Whitney et al, 2016) to specifically target adult brain 5-HT synthesis, which nearly eliminates 5-HT from the entire mouse forebrain. Conditional targeting of adult brain 5-HT synthesis, together with well-established operant methods to robustly assay olfactory psychophysics, allowed to us test whether the adult olfactory system requires 5-HT for fundamental aspects of odor-guided operant behaviors, including odor learning and coarse odor discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Studies provide evidence that altered availability and metabolism of 5-HT may lead to impulsivity [94]. Moreover, studies indicate that 5-HT deficiency leads to a failure of 5-HT-mediated inhibitory control of aggressive behavior and can occur also in adults [11]. Some of the studies have demonstrated decreased levels of 5-HT and 5-HIAA, in the blood, urine, and CSF in individuals with ADHD compared with in healthy controls, but other studies found no differences.…”
Section: Neuropsychiatric Disorders and Serotoninmentioning
confidence: 99%
“…Currently, it is believed that disturbances in the level of 5-HT may be associated with the pathogenesis of few neurological diseases such as migraine [7], epilepsy [8], Parkinson's disease (PD) [1], multiple sclerosis (MS) [9], and amyotrophic lateral sclerosis (ALS) [10] and other disorders (attention-deficit hyperactivity disorder (ADHD) [11], autism spectrum disorder (ASD) [12]). …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, serotonin transporter-deficient mice also showed stressinduced alterations in the adrenocortical stress response as measured by corticosterone metabolites excretion levels (40). 5-HT depleted transgenic animals also seem to have disrupted sleep patterns and display altered muscle and bone structure (41,42). While TPH2 −/− animals did not show altered pain sensitivity they show an increased fear learning (38).…”
mentioning
confidence: 99%